(untitled) (American Journal of Business Management, Economics and Banking, 2024)
This study examined the influence of resource planning and digital resource allocation on project performance in the construction sector of Rivers State, Nigeria. Guided by the positivist paradigm and anchored on the Resource-Based View (RBV) theory, the research aimed to determine the extent to which structured planning and digital tools drive cost, time, and quality outcomes in construction projects. A cross-sectional research design was adopted, and data were collected from 222 management staff across 10 construction firms using a structured 15-item questionnaire measured on a five-point Likert scale. Validity was ensured through expert review and literature grounding, while reliability was confirmed via a pilot study and Cronbach’s Alpha. Pearson Product-Moment Correlation Coefficient was used for data analysis. The findings revealed strong, positive, and statistically significant relationships between resource planning and project performance (r = .709, p < .05), and between digital resource allocation and project performance (r = .739, p < .05). These results demonstrate that effective planning and the integration of digital systems enhance coordination, resource utilization, and stakeholder satisfaction, ultimately improving project efficiency in resource-constrained environments. The study concluded that construction firms that adopt comprehensive planning frameworks and digital allocation platforms are better positioned to achieve competitive advantage through improved project delivery. It recommended that firms strengthen resource planning practices by institutionalizing adaptive planning frameworks, conducting resource audits, and deploying tools such as Microsoft Project for real-time monitoring. Furthermore, firms were advised to enhance digital resource allocation by adopting platforms like BIM and cloud-based systems, investing in staff training, conducting implementation audits, and integrating digital tools with existing workflows to minimize wastage and delays.